MANAJEMEN PEMBELAJARAN PAUD - Azwardi Azwardi Azwardi (UNIVERSITAS BENGKULU, 2015)
The objective of the study is to describe the management of instructional program of early childhood education program. The method of the study is descriptive qualitative study. Thedata were collected through observations, interview, and documentation techniques. Data analysis includes collecting data, data reduction, data display, verification and drawing conclusion. The results of this research described that the planning the instructional based on the KTSP curriculumand syllaby and was not based on the 2013 curriculum. The implementation of the learning program is developed and carried out by the tutors. The technical aspect was done by formal education supervisor and non formal education supervisor.Keyword: early childhood education, learning program and management